MODEL PENINGKATAN KINERJA KARYAWAN HOTEL - Sutrisna, Arga; Putri Lestari, Suci; Arisman, Ari (JURNAL EKONOMI PERJUANGAN, 2025)
This study aims to identify factors that shape employee performance in the Indonesian hotel industry, specifically by analyzing the influence of competence, emotional intelligence, work-life balance, and motivation on employee performance, both collectively and individually. The method used is a survey with data collection through questionnaires distributed to respondents, namely hotel employees in Indonesia, with a focus on Pangandaran Regency. The results of the study revealed that competence, emotional intelligence, work-life balance, and motivation have a significant effect on employee performance, both simultaneously and partially.